Discontinuities in Rap1 activity determine epithelial cell morphology within the developing wing of Drosophila - O'Keefe, David D.; Edgar, Bruce (Developmental biology, 2012)
Mechanisms that govern cell-fate specification within developing epithelia have been intensely investigated, with many of the critical intercellular signaling pathways identified, and well characterized. Much less is known, however, about downstream events that drive the morphological differentiation of these cells, once their fate has been determined. In the Drosophila wing-blade epithelium, two cell types predominate: vein and intervein. After cell proliferation is complete and adhesive cell-cell contacts have been refined, the vast majority of intervein cells adopt a hexagonal morphology. Within vein territories, however, cell-shape refinement results in trapezoids. Signaling events that differentiate between vein and intervein cell fates are well understood, but the genetic pathways underlying vein/intervein cyto-architectural differences remain largely undescribed. We show here that the Rap1 GTPase plays a critical role in determining cell-type-specific morphologies within the developing wing epithelium. Rap1, together with its effector Canoe, promotes symmetric distribution of the adhesion molecule DE-cadherin about the apicolateral circumference of epithelial cells. We provide evidence that in presumptive vein tissue Rap1/Canoe activity is down-regulated, resulting in adhesive asymmetries and non-hexagonal cell morphologies. In particular Canoe levels are reduced in vein cells as they morphologically differentiate. We also demonstrate that over-expression of Rap1 disrupts vein formation both in the developing epithelium and the adult wing blade. Therefore, vein/intervein morphological differences result, at least in part, from the patterned regulation of Rap1 activity.